UPRmt and coordinated UPRER in type 2 diabetes - Kang, Zhanfang; Chen, Feng; Wu, Wanhui; Liu, Rui; Chen, Tianda; Xu, Fang (Frontiers in Cell and Developmental Biology, 2022)
Mitochondrial unfolded protein response (UPRmt) is a mitochondria stress response to maintain mitochondrial proteostasis under stress condition. Increasing evidence suggests that UPRmt participates in diverse pathological processes especially in metabolic diseases such as Type 2 diabetes (T2D). To coordinate biological activities including mitochondrial bioenergetics during stress, cells must coregulate the endoplasmic reticulum (ER) and mitochondria via stress-responsive signaling pathways such as the ER unfolded protein response (UPRER). It is becoming increasingly clear that the protein kinase RNA (PKR)-like endoplasmic reticulum kinase (PERK) signaling pathway can regulate both UPRER and UPRmt. In this review, we discuss current knowledge about mechanisms of UPRmt, and coordinated UPRER and its involvement in T2D.